Subchronic Toxicity of Ethanol Extract of Syzygium polyanthum (Wight) Walp. Leaves on Wistar Rat - Sri Adi Sumiwi; Ade Zuhrotun; Rini Hendriani; Mochamad Rizal; Jutti Levita; Sandra Megantara (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Previous works indicated various pharmacology activities of bay plant (Syzygium polyanthum (Wight) Walp.), however only few studies investigated its toxicity. This work was aimed to study the subchronic toxicity of ethanol extract of this plant.METHODS: White Wistar rats were divided into 4 groups and were treated with 2% of Arabic gum (PGA) suspension, 1000 mg/kg of body weight (BW), 400 mg/kg of BW and 100 mg/kg of BW, respectively. The animals were observed on their body weight, hematology, clinical biochemistry parameters, organ index and histopathology.RESULTS: Flavonoids, tannins, polyphenols, saponins, quinones, monoterpenes and sesquiterpenes were detected in dried leaves and ethanol extract of bay plant. An increase of body weight in male and female groups treated with dose 100 and 400 mg/kg BW compared to controls, was observed. Moreover, there was an increase of white blood cell (WBC) in male and female groups treated with S. polyanthum extracts compared to controls, whereas a decrease of red blood cell (RBC) was observed in male groups treated with S. polyanthum extracts in dose-dependent manner compared to control. No significant changes of RBC were seen in female groups, haemoglobin values were not altered by extract treatment. Photomicrographs of liver, kidney, lungs, heart and spleen histopathology of male and female S. polyanthum extract-treated groups showed no significant alteration compared to controls.CONCLUSION: Our study revealed that S. polyanthum extracts does not show toxicity on the body weight, hematology, creatinine and serum glutamic pyruvic transaminase (SGPT), but fatty liver and necrosis are observed in female rats. This result can be beneficial for plant-based drug discovery, particularly this study provides information about the safety of S. polyanthum to be further developed as candidate of phytopharmaceutics.KEYWORDS: bay plants, salam leaves, hepatotoxicity, necrosis, SGOT, SGPT